An Analysis of Young Clients' Communications About Their Suicidality on a Text Message Helpline: “I'm Scared of What I Might Do to Myself” - Jeanne Van Wyk; Kerry Gibson (Frontiers in Psychiatry, 2022)
BackgroundYouth suicide is a major international concern and prevention is a priority. In most cases suicidal behavior would be preceded by a period of suicidal ideation. Although feeling suicidal is recognized as a risk factor for suicide, there is little research which captures young people's own experience of suicidality in a moment of crisis.AimsThis study aimed to explore young people's own accounts of their suicidality in the moment in which they experienced it.MethodThis qualitative study examined clients' experience of suicidality as communicated during a text message helpline counseling interaction. The data consisted of 125 text transcripts of an interaction during which a client was experiencing suicidality. These were obtained from a New Zealand based youth helpline service. The data was analyzed using thematic analysis.FindingsThe analysis showed that clients' experienced suicidality as a normal part of their life; that it was understood as a form of coping and that it was seen as a legitimate way to communicate distress. Clients described rapid fluctuations in the intensity of their suicidality and a feeling of being out of control. Despite this, they also communicated ambivalence about acting on their suicidality, and a recognition of the need to get help.ConclusionsThis study offered unique insights into young people's experience of suicidality and opens up opportunities for prevention. It underlines the importance of identifying chronic suicidality early and providing intervention and support prior to a suicidal crisis. The findings point to the potential that text counseling services might have in providing support to young people who are experiencing suicidality in the moment that they need this.